Applied financial econometrics in e-commerce - Islam, Sardar M. N., 1950-; Oh, K. B. (Amsterdam ; Boston : Elsevier, 2003)
Deals with the investigation of the contemporary financial issues of the e-commerce market.
Includes bibliographical references and index.
oif 27/08/15
Loan
Keywords: Electronic commerce -- Australia -- Finance -- Econometric models; Stocks -- Australia -- Econometric models; Electronic commerce -- Australia -- Finance -- Econometric models